The Model of Inter-Religious Education in the Perspective of Moderation of Religion: A Case Study at the University of Defense - Sulaiman Girivirya (International Journal of Science and Society, 2023)
After the rolling reform era, Indonesia was once considered a model of a tolerant country. A place where religion and democracy can coexist. However, over the last five years that image has been called into question. The emergence of various phenomena, such as the burning of the house of worship in Tanjung Balai and the mass mobilization to protest the former Governor of DKI Jakarta Basuki Tjahja Purnama (BTP) or who is more familiarly called Ahok, shows the tendency of intolerance in society to spread to several parts of Indonesia. The State Revenue and Expenditure Budget is allocated 20% for education. Ministry of religion, in 2021 allocates 55.88 trillion (83.46%) for education (ed.: religion and religion). With a budget of this size, people often ask whether such a large budget can have a positive impact on Indonesia's progress, especially from the harmony and harmony of the Indonesian people in building the Indonesian nation. Indonesia itself adheres to a mono-religious view which regulates religious and religious education. However, there are also schools or colleges that carry out religious education with an inter-religious model. This article offers a comparison of the views of religious moderation with the views of the managers of the Religious Education course at the Defense University who study religion using an inter-religious model.